LITERATURE REVIEW: THE ROLE AND EFFECTS OF HOSPITAL HEALTH PROMOTION ON HEALTH POLITICS - Neula Armyttha Rizki Ramadhani (The Indonesian Journal of Public Health, 2021)
ABSTRACTAn applicable health system must be integrated with existing health facilities in the community, such as health facilities at hospitals. One of the efforts made by the hospital is hospital health promotion aimed to enable patients and their families to prevent health problems, improve health more independently, and be active in the healing process, of course while being supported by policy regulations. This study aimed to describe the implementation of hospital health promotion as a health political product that certainly affects the degree of public health. This study was a literature review. Data were collected by library research. Based on the results, making a political decision (especially in the health sector) would affect the health of the community, in addition to politics being influenced by the state of public health. The role of hospitals as health promoters could be realized through hospital health promotion with a new preventive paradigm. Moreover, health promotion could also help improve fair and equal health services while still prioritizing quality and promoting preventive and promotive efforts. More numbers of health personnel both in the curative and preventive treatment should be considered for health policymaking to improve health services, especially in hospital settings. Keywords: health promotion in hospital, health politics